Sportology: An Innovative, Interdisciplinary Scientific Wisdom - KAWAMORI, RYUZO (Juntendo Iji Zasshi = Juntendo Medical Journal, 2020)
We proposed a new wisdom called sportology, a scientific approach to the relationship between sports and health. Needless to say, well-trained, non-stressful physical activities are expected to be the most important methods to comprehensively reduce various health problems.　While using “sports” and “health” as keywords to deepen the respective specialized sciences involved, sportology simultaneously integrates each of these specializations, creating opportunities where deepening and integration are possible and giving society more effective and efficient academic achievements.　In 2007, Juntendo University, with the aid of the Ministry of Education, Culture, Sports, Science, and Technology of Japan, established the Sportology Center, where our motto is to “measure precisely whatever we can measure and make measurable what is not measured in human beings.” Our aim for this center is to translate what we have found at the molecular, cell, and animal levels into demonstrable in human beings. With new findings obtained at this center, we will be able to develop new biomarkers and bioimaging techniques with which we will be able to perform more precise diagnosis and treatment. Among numerous new findings obtained by the Sportology Center, some topics are highlighted.